Maria Grzegorzewska on the Dignity of the Teacher - in the Confrontation with Modernity - Bernadeta Szczupał (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
Maria Grzegorzewska was an outstanding expert on pedeutology and a creator of innovative education system of special educators. In this article I will present the role of moral values, which, according to Grzegorzewska, should be distinguished by a special educator. The realization of individual values, including human dignity of the disabled in society, is a fundamental and current job of every special educator. In this article I will draw attention to the deontological dimension of Grzegorzewska's achievements in perspective to create the socio-educational school climate by modern special educators